Global Distribution of Human Protoparvoviruses - Elina Väisänen; Ushanandini Mohanraj; Paula M. Kinnunen1; Pikka Jokelainen; Haider Al-Hello; Ali M. Barakat; Mohammadreza Sadeghi; Farid A. Jalilian; Amir Majlesi; Moses Masika; Dufton Mwaengo; Omu Anzala; et al. (CENTERS DISEASE CONTROL, 2022)
Development of next-generation sequencing and metagenomics has revolutionized detection of novel viruses. Among these viruses are 3 human protoparvoviruses: bufavirus, tusavirus, and cutavirus. These viruses have been detected in feces of children with diarrhea. In addition, cutavirus has been detected in skin biopsy specimens of cutaneous T-cell lymphoma patients in France and in 1 melanoma patient in Denmark. We studied seroprevalences of IgG against bufavirus, tusavirus, and cutavirus in various populations (n = 840), and found a striking geographic difference in prevalence of bufavirus IgG. Although prevalence was low in adult populations in Finland (1.9%) and the United States (3.6%), bufavirus IgG was highly prevalent in populations in Iraq (84.8%), Iran (56.1%), and Kenya (72.3%). Conversely, cutavirus IgG showed evenly low prevalences (0%-5.6%) in all cohorts, and tusavirus IgG was not detected. These results provide new insights on the global distribution and endemic areas of protoparvoviruses.